2012
DOI: 10.1111/j.1558-5646.2012.01799.x
|View full text |Cite
|
Sign up to set email alerts
|

MHC Variation Is Related to a Sexually Selected Ornament, Survival, and Parasite Resistance in Common Yellowthroats

Abstract: Hamilton and Zuk proposed that females choose mates based on ornaments whose expression is dependent on their genetically based resistance to parasites. The major histocompatibility complex (MHC) plays an important role in pathogen recognition and is a good candidate for testing the relationships between immune genes and both ornament expression and parasite resistance. We tested the hypothesis that female common yellowthroats prefer to mate with more ornamented males, because it is a signal of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 71 publications
6
113
0
Order By: Relevance
“…Mask size might be an indicator of good-genes benefits, as males with larger masks weigh more and have higher IgG antibody levels [37,38], and under some environmental conditions, EPY exhibit stronger T-cell-mediated immune responses than within-pair nest-mates [39]. Recently, we found that male mask size and apparent survival are both positively associated with the total number of MHC class II alleles, and susceptibility to malaria infection is associated with the presence of a particular class II allele [40].…”
Section: Introductionmentioning
confidence: 98%
“…Mask size might be an indicator of good-genes benefits, as males with larger masks weigh more and have higher IgG antibody levels [37,38], and under some environmental conditions, EPY exhibit stronger T-cell-mediated immune responses than within-pair nest-mates [39]. Recently, we found that male mask size and apparent survival are both positively associated with the total number of MHC class II alleles, and susceptibility to malaria infection is associated with the presence of a particular class II allele [40].…”
Section: Introductionmentioning
confidence: 98%
“…For example, a global study on humans found that populations with increased pathogen diversity also exhibited elevated MHC diversity [11]. Additionally, associations between specific MHC alleles and pathogen resistance have been demonstrated in humans [12], non-human primates [13], ungulates [14], rodents [15,16], bats [17], birds [18,19], amphibians [20] and fish [21].…”
Section: Introductionmentioning
confidence: 99%
“…These conflict-of-interest diagrams help to illustrate how conflict changes under different social scenarios. A fundamental debate, for example, is whether or not EPP benefits females (Mulder et al 1994;Westneat and Stewart 2003;Arnqvist and Kirkpatrick 2005;Griffith 2007;Dunn et al 2013). The sex that promotes the occurrence of an extrapair mating also critically influences the pattern of sexual conflict over such matings: Male-and female-driven EPP result in opposite patterns of conflict over whether extrapair matings should occur (Petrie and Kempenears 1998) and hence opposite patterns of selection on traits (Fig.…”
Section: Sexual Conflict From Extrapair Matings In Birdsmentioning
confidence: 99%